Effect of a six week in-season training program on wrestling-specific competitive performance - Francino, L.; Villarroel, B.; Valdés-Badilla, P.; Ramirez-Campillo, R.; Báez-San Martín, E.; Ojeda-Aravena, A.; Aedo-Muñoz, E.; Pardo-Tamayo, C.; Herrera-Valenzuela, T. (International Journal of Environmental Research and Public Health, 2022)
The effect of multi-component training on specific performance is under-researched in wrestlers. The aim of this study was to determine the effect of six weeks of multi-component training on The Special Wrestling Fitness Test (SWFT) performances of wrestlers who were preparing for an international championship, and to, additionally, determine their inter-individual adaptive variability. The wrestlers (n = 13; 7 females; all international level) underwent technical-tactical and physical fitness training for the six weeks before the championship, 12 sessions per week (i.e., 36 h per week). Before and after the intervention the athletes were assessed with the SWFT, a wrestling-specific competitive performance test that includes measurements for throws, heart rate response to the SWFT, and the SWFT index. Significant pre-post intervention improvements were noted for throws (pre = 23.5 ± 2.9; post = 24.9 ± 3.6; p = 0.022) and SWFTindex (pre = 14.9 ± 2.2; post = 14.1 ± 2.2; p = 0.013. In conclusion, six weeks of multi-component training improved wrestling-specific competitive performances in highly-trained wrestlers, although with a meaningful inter-subject variability.